In vitro evaluation of enriched brewers' spent grains using bacillus subtilis WX-17 as potential functional food ingredients - Tan, Yong Xing (2022)
Brewers' spent grains (BSGs) are nutritious food processing by-products generated in the brewing industry. In this study, in vitro digestion-fermentation was employed to examine fermented BSG using Bacillus subtilis WX-17 as functional food ingredients. Insoluble fibers in BSG were converted into soluble fibers after fermentation, giving an increase from 6.13 ± 0.42 to 9.37 ± 0.53 mg/100 g BSG. After in vitro digestion of unfermented and fermented BSG, various nutritional components were found to be higher in fermented BSG. Components such as amino acids and fatty acids gave a concentration of 1.635 ± 0.236 mg/mL and 6.35 ± 0.65 mg/mL, respectively. Additionally, vitamin K2 MK7 was detected in fermented BSG with a concentration of 0.00012 ± 0.000005 mg/mL. Probiotics Bacillus subtilis WX-17 was observed to withstand the in vitro digestion. After in vitro fermentation, various short-chain fatty acids namely acetic acid, propanoic acid, and butyric acid were produced at higher amounts for fermented BSG. The concentrations obtained were 124.11 ± 18.72 mM, 13.18 ± 1.38 mM, and 46.25 ± 7.57 mM respectively. As for gut microbiota profile, differential genera such as Bacteroides and Ruminococcus were detected, showing different effects on the intestinal microbiota. This study demonstrates the potential of using microbial fermentation of underutilized BSG to serve as potential functional food ingredients.